Instagram As Buttonscarves Marketing Communication Media In Building Brand Image - Ade Leasfita; Hurdatul Ainiah; Evi Rianti Budhi Prajanti (International Journal of Education, Information Technology, and Others, 2023)
The trend of veil or hijab industry has been growth rapidly in Indonesia as majority of population are Muslims. In the past few years, numerous numbers of local brand entered the hijab market with uniqueness and creativity that offered variety of styles, patterns and colors to satisfy the customers. As the competition became rigid, some of brands utilized social media platform such as instagram to introduce the brand, to promote the products and to build certain image that represent the brands. Buttonscarves was one of local hijab brand that actively using instagram as a marketing communication media which able to deliver the dimensions of brand image such as brand identity, brand personality, brand association, brand attitude and brand competence. By implementing variety of marketing communication tools via instagram, Buttonscarves has able to shape their brand image which known as premium quality and lifestyle icon for hijab. The research aims to understand how to use Instagram as marketing communication media in building the brand image of Buttonscarves. The research used qualitative method with case study approach by collecting data through in-depth-interviews, observations, and documentation. The findings showed that how Buttonscarves implements various marketing communication tools by utilizing features of instagram to build the 5 brand image dimensions.